The behavioral biases on investment decision behavior: Evidence from Indonesia - Yuana, Pusvita; Kornitasari, Yenny; Manzilati, Asfi (Edelweiss Applied Science and Technology, 2024)
The purpose of this study to analyze the behavior of investors in making financial investments in Indonesia. Although the overall financial literacy level in Indonesia has increased, individuals with higher levels of financial literacy tend to make more rational investment decisions. Being well-literate can be interpreted as the personal ability to understand and create financial concepts. However, some individuals still need help understanding investment products and services in Indonesia. This is due to the fact that there are still individuals who invest in illegal products. This study focuses on four biases: overconfidence bias, optimism bias, herding effect, and flexing, using quantitative analysis. The decision to invest is influenced by the thoughts of each investor and their optimistic behavior in seeking the highest return on their investment. This study used primary data with descriptive quantitative analysis. The number of respondents used in the overall research was 400, with criteria for investment products. The result of this study shows that the variable of overconfidence, optimism, and flexing affects the behavior of financial investment decisions. However, the variable bias herding effect does not affect the behavior of financial investment decisions. In conclusion, investors should be more cautious in making investment decisions by paying attention to the variables of overconfidence, optimism, herding effect, and flexing social media in Indonesia.